Elecciones y segregación de población extranjera en Andalucía: Indicadores ante un nuevo panorama político - Relinque-Medina, Fernando; Fernández-Borrero, Manuela Ángela; Vázquez-Aguado, Octavio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
The reality of migration is a global challenge to today’s societies, posing social, economic and political challenges. In recent years, a politicisation of these issues is being observed, leading to “anti-immigrant” political discourses and the defence of ethnocentric and assimilationist values. This has led to an increase in support for populist radical right political formations, which was reflected in Spain in the last elections with the irruption of VOX in April 2019, increasing their support in November 2019. Faced with this situation, the media, networks and social researchers have linked the presence of the foreign population with this fact, studying the population dynamics and segregation in their influence on the vote for right-wing parties. This paper aims to understand this type of relationship in the Autonomous Community of Andalusia, doing so from a municipal territorial approach and broken down by census tracts.